2021
DOI: 10.3390/met11040567
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structuring via Additive Manufacturing to Improve the Performance of Metal and Polymer Joints

Abstract: In order to enhance the joint performance of Ti6Al4V titanium alloy (TC4) and ultra-high molecular weight polyethylene (UHMWPE) for biomedical applications, different structures were fabricated on TC4 surfaces via electron beam melting (EBM) method in this study. Macromorphologies and microinterfaces of TC4–UHMWPE joints produced via hot pressing technique were carefully characterized and analyzed. The effects of different surface structures on mechanical properties and fractured surfaces were investigated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…The morphology of the metal surface plays an important role in the interfacial bonding between the metal and polymer, especially for the effect of microscale mechanical interlocking. , Figure a,b shows the typical 3D morphologies of the chromium-coated steel surface, which can be used for quantifying the surface roughness and topography. It is worth noting that the overall surface morphology of Cr-coated steel was relatively uniform, while there were numerous valleys and ridges on the surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The morphology of the metal surface plays an important role in the interfacial bonding between the metal and polymer, especially for the effect of microscale mechanical interlocking. , Figure a,b shows the typical 3D morphologies of the chromium-coated steel surface, which can be used for quantifying the surface roughness and topography. It is worth noting that the overall surface morphology of Cr-coated steel was relatively uniform, while there were numerous valleys and ridges on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, the performance and service life of polymer− metal hybrid structures are closely related to the interfacial structure and bonding mechanism. 10 In consequence, comprehensively analyzing and uncovering the interface are conducive to the optimization of the preparation process for products. According to the characterization results shown in preceding sections, it is revealed that EAA and steel were intimately bonded via the coated chromium layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are proposals to use 3D FDM printing to create metal-polymer joints, although they are based on 3D printing by applying polymers to polymers, thereby creating a rivet that holds the metal part [51]. Other additive manufacturing methods were used to create the surface shape of the metallic material to enhance the bonding force [52]. No papers have been found describing the direct application of plastic to metal by 3D FDM printing.…”
Section: Introductionmentioning
confidence: 99%